Renal cell carcinoma metastasizing to adenocarcinoma of esophagogastric junction: A rare case of tumor-to-tumor metastasis - Renu Sukumaran; Anitha Mathews; Thara Somanathan; Jayasree Kattoor (Wolters Kluwer Medknow Publications, 2012)
The simultaneous occurrence of two primary tumors in one patient is not uncommon, but one tumor metastasizing to another malignancy is a rare phenomenon. Tumor-to-tumor metastasis was first described by Berent in 1902. Since then fewer than 200 cases have been reported in the literature. In most of these cases renal cell carcinoma acted as a recipient tumor. In tumor-to-tumor metastasis renal cell carcinoma acting as a donor is exceedingly rare and there are no reported cases of adenocarcinoma of the esophagogastric junction acting as a recipient. We present a case of renal cell carcinoma metastasizing to an adenocarcinoma of esophagogastric junction. To our knowledge, this is the first reported case of such a combination.